Fuzzy logic based power system stabilizer for controlling generator speed using Delphi / Mohd Sanusi Safie - Safie, Mohd Sanusi (2003)
This project describes the developed software based on fuzzy logic to control the speed of synchronous generator. The software is applied to synchronous generator as the controller input variable. This fuzzy system is designed not only for generator but also can apply to other machines by setting the fuzzy logic parameter of the program. This program is limited to function with 5 membership functions. Delphi 5 is used to develop this program.